Emergency Response of Iranian Hospitals Against Disasters: A Practical Framework for Improvement. (2nd August 2017) - Janati, Ali; Sadeghi-bazargani, Homayoun; Hasanpoor, Edris; Sokhanvar, Mobin; HaghGoshyie, Elaheh; Salehi, Abdollah
Abstract: Objective: Hospital emergency management is a continuous process that requires monolithic integration of planning and response attempts with local and national schemes. The aim of the current study is to evaluate emergency response by hospitals against potential disasters in Tabriz, north-west Iran. Methods: A cross-sectional study was conducted in the city of Tabriz, in Iran, in 2016. The study population included all hospitals in Tabriz. A total of 18 hospitals were assessed. The hospital emergency response checklist was used to collect data. Tool components included command and control, communication, safety and security, triage, surge capacity, continuity of essential services, human resources, logistics and supply management, and post-disaster recovery. Data entry and analysis were carried out using SPSS software (version 20). Results: The results showed that the emergency response rate of hospitals was 54.26% in Tabriz. The lowest response rates were for Shafaa hospital (18.89%) and the highest response rates were for Razi Hospital (91.67%). The components of hospital emergency response were assessed to be between 48.07% (surge capacity) and 58.95% (communication). Conclusion: On the basis of the World Health Organization checklist, the emergency response rate for hospitals in Tabriz was only 54.26%. Therefore, hospital emergency responses against disasters have to be improved and must be made to reach 100%. It is essential to design a comprehensive framework for hospital emergency response. ( Disaster Med Public Health Preparedness . 2018;12:166–171)